2016
DOI: 10.1177/1420326x16641313
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of ventilation efficiency by changing the shape of glass partition in bathroom of apartment house

Abstract: In the bathroom, the spreading of contaminants may differ depending on whether the shower or toilet is used. The shower and toilet space separated by a glass partition, could affect the spread of contaminants. Computational fluid dynamics analyses were conducted to examine the ventilation efficiency achieved by the glass partition in the bathroom, while a resident was taking a shower and while using the toilet. The following cases were studied: (i) when the top part of the glass partition is open; (ii) when it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…After analyzing restrooms in 140 K-12 public schools in Taiwan, a representative model restroom with the following dimensions is selected as the study subject: 10.65 m × 9.2 m × 3.2 m (height) (Figure 1). In Figure 1c, 1 indicates the aisle in the restroom, 2 is the squatting toilet area in the women's restroom, and 3 is the urinal area in the men's restroom.…”
Section: Study Subjectmentioning
confidence: 99%
See 2 more Smart Citations
“…After analyzing restrooms in 140 K-12 public schools in Taiwan, a representative model restroom with the following dimensions is selected as the study subject: 10.65 m × 9.2 m × 3.2 m (height) (Figure 1). In Figure 1c, 1 indicates the aisle in the restroom, 2 is the squatting toilet area in the women's restroom, and 3 is the urinal area in the men's restroom.…”
Section: Study Subjectmentioning
confidence: 99%
“…In Taiwan, restrooms in K-12 public schools (kindergarten (K) and the 1st through the 12th grade (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)) are frequently accessed and are open to the public, which hinders their management. In particular, restrooms that have been in service for more than 20 years often exhibit problems, such as poor ventilation, inadequate lighting, outdated layouts and designs and limited toilet spaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the forced ceiling-supply and wallexhaust systems had the best odor removal effect among these strategies. Yang and Kim [3] applied computational fluid dynamics (CFD) to analyze the influence of changing the shape of the glass partition on the ventilation performance of an apartment restroom. The results indicated that the use of a glass partition design in a restroom with a shower and a toilet could contribute to good household hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…CFD software is also capable of analysing the air temperature and velocity profiles of the entire building space, including the evaluation of thermal comfort (Pichurov et al, 2014;Risberg et al, 2018). Building types that have been analysed using CFD include educational institutes (Stevanovic et al, 2016;Ghosh et al, 2016;Song and Meng, 2015), offices (Gangisetti et al, 2016;Zhai and Chen, 2006), dwellings (Prakash and Ravikumar, 2015; Barbason and Reiter, 2014;Yang and Kim, 2016) and others, which included naturally aired spaces of various functions (Hamzah et al, 2016;Hajdukiewicz et al, 2013;Wu et al, 2012). Models which represented the actual buildings or building spaces were developed, and all relevant environmental parameters that are essential for simulation purposes, which were either measured in situ or estimated based on the given values in building standards, were then incorporated.…”
Section: Introductionmentioning
confidence: 99%